Knowledge of Cervical Cancer and Associated Factors Among Women Attending Public Health Facilities in Eastern Ethiopia - Wakwoya, Elias Bekele (Cancer Manag Res, 2020)
PURPOSE: This study was done to assess women’s knowledge of cervical cancer and associated factors. MATERIALS AND METHODS: We conducted a facility-based cross-sectional study in eastern Ethiopia from January 1 to May 30, 2019. A convenient sampling technique was used to include 1181 women in this study. Information on socio-demographic characteristics, sexual history, knowledge and awareness of women was collected using face-to-face interview. The data were cleaned, coded and entered into EPI‑info version 3.5.4 and then exported to Statistical Package for Social Science version 23.0 software for analysis. The associations between independent variables and outcome variables were assessed using bivariate and multivariable logistic regressions. The results of these analyses were reported as odds ratios with 95% confidence intervals. We declared statistically significant variables at a p-value less than 0.05. RESULTS: Nearly half (574, 48.6%) of the participants have ever heard about cervical cancer. One hundred and thirty-nine (24.2%) of them did not know any of the risk factors. The majority of them mentioned bleeding after intercourse (329, 57.4%) as a symptom of the disease. Overall knowledge assessment revealed that 288 (55.7%) participants had adequate knowledge about cervical cancer. Participants’ age in the range of 40–49 years (AOR: 2.58, 95% CI 1.99–5.57), having educational level above 12th grade (AOR: 12.11, 95% CI 4.57–32.09) and receiving information about the disease from healthcare professionals (AOR: 2.72, 95% CI 1.69–4.37) were independently associated with adequate knowledge of cervical cancer. CONCLUSION: The knowledge of women towards cervical cancer in our study area was inadequate. The respondents’ age, educational status and source of information were independently associated with study participants’ knowledge of cervical cancer. Young women with no formal education should get special focus in prevention strategies and we also recommend regular and effective counselling, and education about cervical cancer at health institutions.